Metacomics – a poetics of selfreflection in Bill Watterson's Calvin and Hobbes and Pádár and Koska's 'Lifetime Story'. Issue 1 (1st April 2014) - Szép, Eszter
This article examines the ways, modes, tools and categories of medium-specific self-reflexivity in comics. I approach the genre of metacomics in the light of theories of metafiction, as well as W. J. T. Mitchell's concept of 'metapicture'. As several scholars regard comics as a form of literature, I think testing the ideas of metafiction on comics has legitimacy. We can define metafiction with Hutcheon's words as 'the new need, first to create fictions, then to admit their fictiveness, and then to examine critically such impulses'. In this article I argue that metacomics is similar, though it features self-reflexive elements not only on the level of plot or (textual) narration, but also in its very form and layout. Mitchell's approach from the field of iconology, and his typology of metapictures serves as a model for conceptualizing metacomics. According to Mitchell, '[m]etapictures are pictures that show themselves in order to know themselves: they stage the "self-knowledge" of pictures'. This article builds on Mitchell's category of the 'speaking metapicture', which is strikingly close to comics. Thus I simultaneously rely on a framework for analysis from literary theory, and another one from iconology, in order to examine the self-reflexive methods bound to the comics medium. Following Hatfield, I approach comics as an art form of four kinds of tension, namely code vs code, single image vs image-in-series, sequence vs surface and text as experience vs text as object. I am interested in the theory and typology of the kinds of reflection on the medium of comics that are made possible by these tensions. I am examining the works of Bill Watterson, and the Hungarian authors Zoltán Koska and Ádám Pádár.